Conditions for Sustainable and Secure Economic Development in Georgia: Achievements and Problems - Kakhaber Tsimintia (Modern Scientific Technology, 2025)
The paper discusses the place and role of economic security and sustainable economic development in the development of the country. The main economic interests of Georgia are presented. The existing conditions for the possibility of sustainable economic development of Georgia are analyzed using relevant indicators, the existing problems of sustainable and secure development of the Georgian economy are presented, and the necessary recommendations for overcoming them are presented